Parotid malignancies are not homogenous in terms of their presentation on dynamic MRI – a preliminary report. (1st February 2017) - Mikaszewski, Bogusław; Markiet, Karolina; Smugała, Aneta; Stodulski, Dominik; Szurowska, Edyta; Stankiewicz, Czesław
Abstract: Conclusion: At least two groups of parotid malignancies exist, including one whose parameters of dynamic MRI closely resemble those of pleomorphic adenomas. Also tumors with long time to peak enhancement after administration of a contrast agent (Tpeak ) and low washout rate (WR) should be considered malignant, especially single masses with concomitant lymphadenopathy located within the deep parotid lobe. Objective: To verify if malignant tumors of the parotid are homogeneous in terms of parameters of preoperative dynamic MRI: Tpeak and WR. Methods: The retrospective analysis included 221 surgical patients with parotid tumors. Aside from fine needle biopsy, pre-operative examination included dynamic and diffusion-weighted MRI. Final diagnosis was based on histopathological examination of the surgical specimen. Results: Twenty-four of 221 (10.8%) malignant lesions were identified. Using k -means clustering based on Tpeak and WR values, two distinct clusters of parotid malignancies were identified. The cut-off value for Tpeak optimally differentiating between the clusters was 140 s; the cut-off value for WR could not be identified. The two clusters did not differ in terms of dynamic and diffusion-weighted MRI parameters, patient age, sex and prevalence of lymphadenopathy. Significant inter-cluster differences were found in the prevalence of deep parotid lobe involvement and presence of a single mass.